ONC201 (Dordaviprone) Induces Integrated Stress Response and Death in Cervical Cancer Cells - Sneha O. Pathak; Sonal M. Manohar (Biomolecules)
Cervical cancer is a leading cause of death in women globally. Systemic chemotherapy offers only limited therapeutic benefit for advanced-stage disease due to toxicity and drug resistance. ONC201 (also known as TIC10 or dordaviprone) is a TRAIL (TNF-Related Apoptosis-Inducing Ligand) and cIpP (caseinolytic protease) agonist currently in Phase II clinical trials for different types of cancer. In the present study, we investigated the anticancer potential of ONC201 in HPV-positive cervical cancer cell lines. ONC201 exerted significant cytotoxicity and inhibited the clonogenic potential of cervical cancer cells. It induced integrated stress response along with S/G2-M arrest and apoptosis in both cell lines. Yet, surprisingly, well-known targets of ONC201 viz. TRAIL, DR5 (death receptor 5) and cIpP were found to be upregulated only in HeLa but not in SiHa cells in response to ONC201 treatment. In addition, expression of BNIP3 and Beclin-1 (both involved in regulation of autophagy) increased in response to certain doses of ONC201. Furthermore, ONC201 exhibited synergism in combination with standard drugs against cervical cancer cells. This study provides a proof of concept for the anticancer activity of versatile drug ONC201 against cervical cancer cells and also delineates its mechanism of action.